2017
DOI: 10.1515/pjfns-2017-0016
|View full text |Cite
|
Sign up to set email alerts
|

Colour Stability and Lipid Oxidation of Beef Longissimus Lumborum under Different Packaging Conditions

Abstract: The objective of this study was to investigate the colour stability and lipid oxidation of beef under different packaging methods. The muscles longissimus lumborum were randomly packed in vacuum or modifi ed atmosphere packaging (MAP, 80% O 2 , 20% CO 2 ). Both packages were aged at 4°C for 7, 14 and 21 days. After each ageing time, samples were displayed in a refrigerator for 2, 4 and 6 days. Colour stability, lipid oxidation and their correlation were determined. Beef under vacuum packaging showed higher a* … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 24 publications
(18 reference statements)
0
2
0
Order By: Relevance
“…Owing to the oxygen content in the modified atmosphere ( MA ), the packaging of high or low (including vacuum) oxygen content is distinguished. The high-oxygen MA (70% ÷ 80% O 2 , 20% ÷ 30% CO 2 ) is commonly used in the food industry to preserve and even improve the red color of meat, especially for meat with high heme pigments content, including goose meat (Fernandes et al, 2014 ; Santos et al, 2015 ; Bonny et al, 2017 ). However, such atmospheric composition has limitations due to its oxidative activity.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to the oxygen content in the modified atmosphere ( MA ), the packaging of high or low (including vacuum) oxygen content is distinguished. The high-oxygen MA (70% ÷ 80% O 2 , 20% ÷ 30% CO 2 ) is commonly used in the food industry to preserve and even improve the red color of meat, especially for meat with high heme pigments content, including goose meat (Fernandes et al, 2014 ; Santos et al, 2015 ; Bonny et al, 2017 ). However, such atmospheric composition has limitations due to its oxidative activity.…”
Section: Introductionmentioning
confidence: 99%
“…To reduce the unbeneficial effects of oxidation processes on meat quality, the meat industry uses vacuum packaging, which exerts a strong oxidation-inhibiting effect. Bonny et al [2017] showed that TBAR levels were the lowest in vacuum-packed beef samples compared to the modified atmosphere-packed (MAP) samples. Similar results were observed for carbonyl group content, where vacuum packaging presented significantly lower carbonyl content after 10 days than MAP treatments.…”
Section: Introductionmentioning
confidence: 99%